KEMAMPUAN MANAJERIAL DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH - Johannes Johannes (Hijri, 2017)
Implementation of School Based Management (SBM) presents schools as an institution with authority and authority that is no longer dependent on centralistic policy and bureaucracy, where schools are no longer treated as educational institutions that receive instruction only without creativity adjustments and are positioned as institutions that are controlled only Strict, so it does not have the freedom to move in managing the resources they have to achieve the optimal quality of school. A major challenge in the implementation of SBM is the ability of educational resources in terms of leadership integrity, where the principal is required to have the ability to perform managerial and leadership functions. In the implementation of MBS, there will be undesirable discrepancies, since the policy demands a mental change of the education apparatus and the wider community that has been so long patterned is not easy. The current application of MBS still does not refer to the actual concept, where until now the mastery of concepts relevant to the principal's tasks has not been widely understood by the school principal, so managerial and principal leadership at this time has not run properly. Meanwhile, in the implementation of SBM, the principal is required to be able to carry out managerial and leadership functions in the school. MBS is a model of school management characterized by extensive autonomy in schools, participation and high community participation to improve the quality of education within the national policy framework and applicable legislation.